(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Livestock species play an important role in the agro-based economy of Bangladesh. The present study was performed to determine the magnitude and trends of clinical diseases and disorders in native sheep in order to design a set of strategies to be applied for the prevention and control of these problems in this farm. A total of 1870 indigenous sheep at BLRI sheep research farm, Savar, Dhaka, Bangladesh were included under this study. The study was carried out during the period from January 2012 to December 2014. Diagnoses and records of clinical diseases and disorders were based on pertinent clinical history, clinical findings and laboratory tests. The major clinical diseases and disorders were determined diarrhoea (5.18%), malnutrition (2.85%), lameness (1.93%), pneumonia (1.02%), alopecia (0.88%), tapeworm infection (0.81%) and fever (0.51%). In case of seasons, the highest incidence was found during rainy season (2.26%) followed by winter (5.85%) and summer (4.25%); whereas in respect of age groups, the highest incidence was found in growing sheep (26.14%) followed by adults (12.15%) and lambs (10.93%). Although some diseases and disorders took place in the BLRI sheep research farm, the incidence were very low and most of the infectious diseases did not occur because of proper management of the farm particularly regular deworming, dipping and vaccination. Moreover, on the basis of these findings measures should be taken for further prevention of such diseases and manifestations. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 37-46